2017
DOI: 10.1080/0284186x.2016.1267873
|View full text |Cite
|
Sign up to set email alerts
|

Association between late effects assessed by physicians and quality of life reported by head-and-neck cancer survivors

Abstract: Physician-assessed moderate to severe hoarseness and mild, moderate, or severe dysphagia are associated with clinically relevant decreases in patient-reported quality of life and functioning. Fibrosis and xerostomia of any severity were not associated with changes in any scale of functioning in this study population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 22 publications
4
11
1
1
Order By: Relevance
“…There were statistically significant differences between the patients with T A B L E 4 MDADI scores before treatment (baseline) and follow-up (6 and 12 months) and a control group without dysphagia. Comparisons of changes within and between groups 4 This further strengthens the use of this threshold value in clinical praxis.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…There were statistically significant differences between the patients with T A B L E 4 MDADI scores before treatment (baseline) and follow-up (6 and 12 months) and a control group without dysphagia. Comparisons of changes within and between groups 4 This further strengthens the use of this threshold value in clinical praxis.…”
Section: Discussionsupporting
confidence: 59%
“…3 Swallowing problems are often associated with reduced health related quality of life (HRQL), morbidity, anxiety and depression. 3,4 Dysphagia is often monitored through functional assessment of swallowing ability, by for example videofluoroscopy or fiberoptic endoscopic evaluation of swallowing. In addition to this, instruments to measure the degree and impact of dysphagia are useful when evaluating the treatment and rehabilitation outcome and needs.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to previous studies that reported patient-related factors such as, gender [16,19,20] and nancial burden [18,44,45], tumor-related factors such as advanced tumor stage [21][22][23], location of HNC [25][26][27][28][29] and type of treatment [15,25,30] ,this study also identi ed that female sex, low income (who can't cover their medical expenses), suffering from laryngeal/ hypo pharyngeal cancer, suffering from advanced tumor are key determinants of poor QoL related to swallowing problems in HNC patients. These results have direct implications at improving the care of HNC patients by highlighting the need to incorporate swallowing function in the assessment and clinical management of patients.…”
Section: Discussionsupporting
confidence: 82%
“…Factors predictive of poor quality of life (QoL) due to dysphagia could be patient-related [15] such as smoking [16][17][18], alcohol abuse [16], age [16,18,19], lean mass [16], and gender [16,19,20]; tumorrelated [15] such as advanced tumor stage [17,[21][22][23][24], location of HNC [25], such as patients with tongue [26], buccal [27], hypo pharyngeal [28] and laryngeal [29] tumors had worse dysphagia related QoL, type of treatment [15,25,30] in which higher level of dysphagia and lower QoL scores among patients who had radiotherapy [19], [31], [32], [29,33] and surgery [19,34,35] and patients treated with concomitant chemotherapy have an exacerbated dysphagia and dietary problems [36]. Deterioration in swallowing function through time were also reported from before treatment to 3 months [3,37,38] and 6 months [17,39] post treatment with some improvements at later times [17,37,38,…”
Section: Introductionmentioning
confidence: 99%
“…Je nach Lokalisation und Größe eines Tumors sowie der Art der notwendigen onkologischen Therapie werden Prävalenzen von 5 bis 78 % dieser Folgeerkrankung in der Literatur angegeben [1][2][3][4]. Schluckbeschwerden sind mit tiefgreifenden sozialen, emotionalen und sozioökonomischen Auswirkungen assoziiert [5][6][7][8][9]. Moderne Diagnostik und modernes Management einer solchen Schluckstörung erfordern daher einen multidimensionalen Ansatz.…”
Section: Introductionunclassified